Sistem Pendeteksi Kebocoran Gas dan Kebakaran Menggunakan Node MCU ESP 8266 dengan Notifikasi Telegram - Dwi Waluyo, Bakti; Aulia Rahman S, Muhammad; Haryanto Sinaga, Denny (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2024)
Gas leaks are one of the risks that occur due to improper installation of LPG cylinders. Therefore, a fast and reliable gas leak detection tool with an Internet of Things (IoT)-based approach is needed as an effective solution. This study designed a tool based on the Arduino Uno microcontroller and the Esp8266 module for remote gas leak monitoring. The gas sensor is used for real-time leak detection and sends warning notifications through the IoT network. The application of IoT technology in this system not only improves the safety of LPG use but also allows integration with modern technological developments. This tool is an innovative solution in creating a safer and more efficient environment in LPG cylinder installation.